Analysis of GCMs for prediction of precipitation for Hoshangabad region of Madhya Pradesh - ANKIT BALVANSHI; H. L. TIWARI (Journal of Agrometeorology, 2018)
Ten general circulation models (GCMs) – BCCR-BCCM2.0, Can-ESM2, CGCM3, CSIRO-Mk3.0, GFDL-CM2.0, GFDL-CM2.1, GISS, HADCM3, HADGEM1 and MIROC3.2 were analysed for prediction of precipitation for Hoshangabad region, Madhya Pradesh India. The performance indicator, skill score (SS),technique for order preference by similarity to an ideal solution (TOPSIS) techniques were employed for the selection of the best GCM. The multi-criterion decision making method (MCDM), technique TOPSIS was employed to evaluate and rank the 10 GCMs. On the basis of skill score and TOPSIS, GCMs Can- ESM2, CGCM3, GFDL2.0, HadCM3, MIROC3.2 is recommended for the study area. It is also found that GCMs CSIRO-Mk3.0 and GISS occupied the last two positions for Hoshangabad region, M.P., India.